Impact of Exercise Modalities on Upper Extremity Spasticity in an Adult with Quadriplegic Cerebral Palsy: A Case Report - Juntack Oh; Michele Aquino (Journal of Functional Morphology and Kinesiology, 2025)
Background: Spasticity, a hallmark of quadriplegic cerebral palsy (CP), severely impacts mobility and quality of life. While exercise is known to enhance fitness and motor function in individuals with CP, its specific efficacy in reducing upper extremity spasticity remains insufficiently studied. This research investigated the effects of weight-resistance exercise (RE), hand cycle bike exercise (BE), and aquatic exercise (AE) on upper extremity spasticity in an adult with quadriplegic CP. Method: The participant was a 35-year-old individual with quadriplegic spastic CP, presenting severe spasticity in the right upper extremity and lower limbs, and milder left arm involvement. Dependent on a power wheelchair, they were cognitively intact, college-educated, and had participated in a community exercise program for five years. Over nine weeks, the participant completed 18 sessions—6 per modality of RE, BE, and AE—with each session held twice weekly for 50 min. Spasticity was assessed using the Modified Ashworth Scale (MAS) before and after sessions, with comprehensive pre- and post-intervention evaluations. Result: Total MAS scores decreased significantly from 2.76 to 2.33 (p < 0.05). AE yielded the largest reduction (2.81 to 2.10), followed by BE (2.75 to 2.36) and RE (2.72 to 2.54). ANOVA confirmed AE’s superior efficacy (F(2,15) = 27.20, p < 0.001, ηp2 = 0.78), with a 0.33 reduction overall. Conclusions: AE was most effective, likely due to buoyancy, followed by BE, with RE showing the least impact. These findings highlight aquatic interventions as promising for spasticity management in CP, necessitating further longitudinal, multi-participant research.